Research on turbulence model for simulation of wind flow in mountain areas of micro-topography. Issue 1 (1st March 2023) - Yin, Yuan; Li, Yangsen; Lin, Ruizong; Liu, Zhiwei; Fu, Benzhao; Huang, Guo; Zhang, Hongjie
Abstract: The accuracy of wind flow simulation in mountain area in micro-topography is related to discrete scheme, turbulence model and wall function. In this paper, the standard hill model is adopt to analyze the calculation accuracy of different turbulence models. Four turbulence models, including RNG k-ε, k-ω, SST k-ω and TSST k-ω, were used in the calculation, and were compared with the result of wind tunnel test. The calculation results with the second-order upwind scheme, the SST or TSST turbulence model and the scalable wall function are basically consistent with results of wind tunnel test.